Precision feeding strategy for growing pigs under heat stress conditions - dos Santos, Luan Sousa [UNESP]; Pomar, Candido; Campos, Paulo Henrique Reis Furtado; Silva, Welex Candido da [UNESP]; Gobi, Jaqueline de Paula [UNESP]; Veira, Alini Mari [UNESP]; Fraga, Alicia Zem [UNESP]; Hauschild, Luciano [UNESP] (Oxford University Press (OUP), 2018)
This study evaluated the responses of individual daily precision (IPF) and conventional 2-phase (CON) feeding systems (FS) in terms of pig growth performance, nutrient balance, serum parameters, and meal patterns of growing pigs reared under thermoneutral (TN: 23 °C) and heat stress (high temperature [HT]: 30 °C) conditions. The animals in each treatment were assigned on the basis of equal BW to the experimental treatments (12 animals per treatment at 41.0 ± 4.87 kg of BW). The experiment lasted 55 d (phase 1 from days 0 to 27 and phase 2 from days 28 to 55). Pigs fed CON received within each phase a constant blend of diets with high and low nutrient density supplying the estimated nutrient requirements of the group, whereas the IPF pigs received daily a personalized blend providing the estimated amount of nutrients according to individual feed intake and body weight information. Body mineral content, and lean and fat masses were assessed through dual-energy X-ray absorptiometry at the beginning and end of each phase. Data were analyzed using a linear mixed-effect model, with fixed effects of the FS, temperature (AT), and the 2-way interaction between FS and AT and random effects of blocks. In relation to CON pigs, IPF pigs reduced (P < 0.05) Lys (19%), protein (16%), and P (14%) intake without impairing (P > 0.05) body composition. Nitrogen excretion was 24% lower (P < 0.05) in IPF pigs than in CON pigs; however, both groups had similar N retention efficiency thoroughly the trial. Amount of time feeding, feed intake rate, and feed intake per meal were 15% lower (P < 0.05) in pigs raised under HT than under TN conditions. During the phase 2, only amount of time feeding, feed intake rate, and feed intake per meal were decreased (P < 0.05) in pigs under HT conditions during nocturnal (2000 to 0500 h) and diurnal (0501 to 1959 h) periods. Haptoglobin levels were affected by the AT, showing an increase of 70% and 43% in HT at 28 and 55 d of the experiment, respectively. Pigs raised under HT conditions had 10% lower (P < 0.05) serum albumin concentration at day 55 than those under TN conditions. For serum urea concentrations, IPF pigs had 28% lower (P < 0.01) levels than CON pigs. Even though HT conditions considerably reduced growth performance and activated inflammatory responses in growing pigs, IPF was not able to rescue performance during HT; however, it was equally effective at improving nutrient utilization and maintaining body composition in HT and TN conditions.
Keywords: Heat stress; Nutrient utilization; Nutrition; Precision feeding; Reduced protein; Tropical conditions